Monitoring of Allogeneic Islet Grafts in Nonhuman Primates Using MRI. Issue 8 (August 2015) - Wang, Ping; Schuetz, Christian; Vallabhajosyula, Prashanth; Medarova, Zdravka; Tena, Aseda; Wei, Lingling; Yamada, Kazuhiko; Deng, Shaoping; Markmann, James F.; Sachs, David H.; Moore, Anna
<x xml:space="preserve">Abstract</x> Background Information regarding the longevity of transplanted pancreatic islet grafts could provide valuable information for treatment options. In our previous studies, we showed that isolated autologous pancreatic islets could be labeled with iron oxide nanoparticles and monitored after transplantation using MRI. Here, we report on in vivo monitoring of a secondary damage that occurs at the later stages because of allogeneic immune rejection. Methods In the proof-of-principle studies, iron oxide-labeled autologous pancreatic islets were transplanted under the renal capsules of nonhuman primates. To demonstrate acute graft loss, the animals were injected with streptozotocin. Graft monitoring was performed by in vivo MRI. Next, iron oxide-labeled allogeneic islets were transplanted into the liver and monitored by MRI after withdrawal of immunosuppression. Results In autologous model, we observed a pronounced drop in graft volume after streptozotocin challenge as assessed by MRI. In allogeneic model of islet transplantation, there was an initial islet loss after the procedure followed by relative stabilization of the graft volume. After immunosuppression was discontinued, there was a noticeable drop in graft volume that gradually continued during the course of the study. Importantly, the loss of graft volume observed on MR preceded the raise in blood glucose. Conclusions This study demonstrated that in vivo MRI was able to reveal graft volume loss before any changes in blood glucose that can be measured by standard methods. We believe that these results could provide means for clinicians to follow islet fate noninvasively and longitudinally using clinically relevant scanners.